Quantitative analysis of a switched mode power supply employing a single DSP controller - Espina, Evan M. (2004)
The control of switched mode power supply (SMPS) systems has been predominantly through analog control. With the advent of digital signal processing (DSP) technology, digital control systems have become cost and energy efficient. This development has led to an increased interest in the digital control of SMPS systems. Designers are faced with the challenge of making the transition from the existing analog environment to the new digital space. In this thesis, the digital control of a Boost Regulator with Power Factor Correction (PFC) and a Phase Shifted Full Bridge DC/DC Converter using a single DSP controller was implemented and evaluated. Soft switching techniques were applied to minimize switching losses and electromagnetic interference (EMI) in high frequency operation. The dynamic performance of the system was investigated and compared to a system employing traditional analog control.